2002
DOI: 10.1210/jcem.87.4.8374
|View full text |Cite
|
Sign up to set email alerts
|

Flaxseed Improves Lipid Profile without Altering Biomarkers of Bone Metabolism in Postmenopausal Women

Abstract: The risk of cardiovascular disease and osteoporosis drastically increases at the onset of menopause. Phytoestrogens have been suggested to inhibit bone loss and protect the cardiovascular system, in part by improving lipid profiles. The purpose of the present study was to examine the effects of flaxseed, a rich source of the phytoestrogens called lignans, on lipid metabolism and biomarkers of bone turnover in postmenopausal women. Postmenopausal women who were not on hormone replacement therapy were assigned t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(37 citation statements)
references
References 42 publications
2
34
0
1
Order By: Relevance
“…In the few clinical and animal trials that have examined the effects of FS on bone turnover, mixed findings have been reported (Abdelkarem et al 2011;Babu et al 2000;Brooks et al 2004, Farmer et al 2007Griel et al 2007;Lucas et al 2002;Ward et al 2001aWard et al , 2001b. Our finding that FS alone did not impact serum markers of bone turnover is in agreement with most previous data reporting little or no effect on BMD, bone strength, and bone turnover (Brooks et al 2004;Dodin et al 2005;Farmer et al 2007;Lucas et al 2002;Sacco et al 2009). However, it is difficult to compare our current findings with these previous studies since they were conducted in various clinical populations (e.g., healthy postmenopausal women, middle-aged men) and animal models (e.g., growing rats and gilts), and they were of varying durations (6 weeks-12 months).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In the few clinical and animal trials that have examined the effects of FS on bone turnover, mixed findings have been reported (Abdelkarem et al 2011;Babu et al 2000;Brooks et al 2004, Farmer et al 2007Griel et al 2007;Lucas et al 2002;Ward et al 2001aWard et al , 2001b. Our finding that FS alone did not impact serum markers of bone turnover is in agreement with most previous data reporting little or no effect on BMD, bone strength, and bone turnover (Brooks et al 2004;Dodin et al 2005;Farmer et al 2007;Lucas et al 2002;Sacco et al 2009). However, it is difficult to compare our current findings with these previous studies since they were conducted in various clinical populations (e.g., healthy postmenopausal women, middle-aged men) and animal models (e.g., growing rats and gilts), and they were of varying durations (6 weeks-12 months).…”
Section: Discussionsupporting
confidence: 90%
“…The 10% FS level was chosen for the present study because it is attainable in the human diet, representing an intake of 25-50 g or 2½-5 tablespoons of FS per day. Moreover, 10% FS represents a level that has been shown to reduce tumour growth, serum, or plasma cholesterol, and atherosclerosis in animal and clinical models (Chen et al 2007;Dupasquier et al 2007;Lindahl et al 2011;Lucas et al 2002;Thompson et al 2005). The sham-operated group was fed the BD and was included as a positive control group (POS).…”
Section: Study 1: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Other plasma lipid parameters were not changed significantly. Many studies are focused on the effect of either probiotics (reduction in TG, TC, LDL and HDL cholesterol levels; Jin et al 1998;Wang et al 2009) or flaxseed (no effect; Lemay et al 2002;Lucas et al 2002) on lipid metabolism in animals. Several authors discussed the effect of synbiotics on cholesterol levels (Liong et al 2007), who observed decrease in HDL cholesterol, but in hypercholesterolaemic pigs.…”
Section: Plasma Lipid Levelmentioning
confidence: 99%
“…Flaxseed being a rich source of plant lignan precursors for enterolactone might provide cardiovascular benefits [6]. Investigations into the health effects of whole flaxseed or flaxseed products (for example, defatted flaxseed meal, flaxseed extracts) in human clinical trials and animal models have shown beneficial changes in blood lipid profiles [7,8] and protection against some types of cancer [9,10].…”
Section: Introductionmentioning
confidence: 99%